Coordinated Role of Nitric Oxide, Ethylene, Nitrogen, and Sulfur in Plant Salt Stress Tolerance - Badar Jahan; Faisal Rasheed; Zebus Sehar; Mehar Fatma; Noushina Iqbal; Asim Masood; Naser A. Anjum; Nafees A. Khan (Stresses, 2021)
Salt stress significantly contributes to major losses in agricultural productivity worldwide. The sustainable approach for salinity-accrued toxicity has been explored. The use of plant growth regulators/phytohormones, mineral nutrients and other signaling molecules is one of the major approaches for reversing salt-induced toxicity in plants. Application of the signaling molecules such as nitric oxide (NO) and ethylene (ETH) and major mineral nutrient such as nitrogen (N) and sulfur (S) play significant roles in combatting the major consequences of salt stress impacts in plants. However, the literature available on gaseous signaling molecules (NO/ETH) or/and mineral nutrients (N/S) stands alone, and major insights into the role of NO or/and ETH along with N and S in plant-tolerance to salt remained unclear. Thus, this review aimed to (a) briefly overview salt stress and highlight salt-induced toxicity, (b) appraise the literature reporting potential mechanisms underlying the role of gaseous signaling molecules and mineral nutrient in salt stress tolerance, and (c) discuss NO and ETH along with N and S in relation to salt stress tolerance. In addition, significant issues that have still to be investigated in this context have been mentioned.